THE EFFECT OF DIFFERENT STRUCTURE AND GRADIENT INFILL ON MECHANICAL BEHAVIOR POLYLACTIDE ACID MATERIALS (PLA) - Akbar, Imam; Hidayat, M Rizky; Rawani, Dewi; Veranika, Rita Maria; Al-Faritzie, Hariman; Romli, Romli (AUSTENIT, 2023)
The purpose of this study is to analyze the effect of our gradient infill on the mechanical behavior of polylactide acid (PLA) materials resulting from 3d printing, which has an impact on the efficiency of material use while still providing good mechanical support. In this study, the specimens were designed using nTopology software and there were 4 variations of the structure, namely square, honeycomb, diamond, and gyroid, each of which was made gradient and non-gradient, then a bending test was carried out to determine its mechanical behavior thats PLA materials. The results of this study indicate that a comparison between specimens with gradient and non-gradient models with 50% porosity can increase the deflection of the specimen, namely square 15.7-19.1 mm, honeycomb 16.3-20.6 mm, Diamond 19.7-21.8 mm, and gyroid 20.3-22.1 mm, with an average deflection of 2.04 mm. In addition, there is a linear correlation of the relationship between thickness to deflection and flexural modulus whereas the thickness value increases, the deflection and flexural modulus will increase. The conclusion of this research is that giving a gradient to the structure can improve mechanical behavior, especially deflection.